(untitled) (Revista Innova Educación, 2022)
This research article rescues the origin and evolution of the learning evaluation process in distance education programs that have been offered in the Mexican educational system for a century. First, the historical and current context of evaluating distance education in Mexico is addressed. The method for the analysis of the information corresponds to the cycle of hermeneutic interpretation that allows triggering historical-social elements to discuss the findings found. The results are presented in the following sections: a) educational programs offered at a distance, b) elements of the formal curriculum and pedagogical approaches and c) principles of evaluation-feedback-digital technologies used in times of the covid-19 pandemic. Finally, it concludes with a reflection on the controversies in evaluating learning in the evaluation process in times of the covid-19 pandemic.